Respuestas
Respuesta dada por:
1
Respuesta:
a = 2
Explicación paso a paso:
f(x) = 2x + 7
- f(a) = 2a + 7
- f[2a + f(a)] = f(2a + 2a + 7)
f[2a + f(a)] = f(4a + 7)
- f(4a + 7) = 2 . (4a+7) + 7
f(4a + 7) = 8a + 14 + 7
f(4a+7) = 8a + 21
Entonces:
8a + 21 = 37
8a = 37 - 21
8a = 16
a = 16/8
a = 2
- VERIFICACIÓN:
f[2a + f(a)] = f( 2 . 2 + 2 . 2 + 7) = f(15)
f(15) = 2 . 15 + 7
f(15) = 30 + 7
f(15) = 37 VERIFICA
Preguntas similares
hace 3 años
hace 3 años
hace 3 años
hace 6 años
hace 6 años
hace 8 años
hace 8 años